GAMBARAN PERAN PERAWAT TERHADAP PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI RUANG ICU - Nurhanif, Nurhanif; Purnawan, Iwan; Sobihin, Sobihin (Journal of Bionursing, 2020)
Background. ICU patients ' spirituality is very important. Spirituality will be the way the patient searches for the meaning of life, including a disease-related affliction. In spiritual needs, nurses who view the patient holistically play an important role.Methods. This research is a phenomenologically approached qualitative descriptive form. While the collection of participants by purposeful sampling method.Results. The results of this study found the 8 themes of 5 special purposes. These themes are: 1) definition of spirituality, 2) function of spirituality, 3) the factors of spiritual distres, 4) the characteristics of patients with spiritual distres, 5) the act of independent nurse in fulfillment spiritual needs, 6) the act of collaboration nurse in fulfillment spiritual needs, 7) the obstacles fulfillme.Conclusion. Eight topics describe nurses ' understanding of spirituality, nurses ' effort in meeting spiritual needs, obstacles in meeting spiritual needs, and awareness of the role of nurses in meeting the spiritual needs of patients in the ICU.